Application of Progressive Muscle Relaxation in the Treatment of Psychosomatic Diseases - Hou Yongmei (Disease and Health: Research Developments Vol. 8, 2025)
Background: Progressive muscle relaxation (PMR) is a relaxation therapy that has been applied in the clinical treatment of psychosomatic diseases. Objective: To introduce the concept, principle and development process of progressive muscle relaxation, with a focus on reviewing its application in the treatment of psychosomatic diseases. Methods: Taking “Progressing Relaxation” or “Progressive Muscle Relaxation Training” or “relaxation and relaxation effect” as keywords, a literature retrieval is conducted to search for academic full-text literature published in Chinese or English in the past twenty years. The literature sources included journals, dissertations, and conference papers from databases including PubMed, Web of Science, CINAHL Plus, Scopus, Embase, PsycINFO, and CNKI. Results: Twenty-one articles were included. Previous literature has shown that progressive muscle relaxation is simple, easy to implement, has no side effects, does not require specialized equipment, and can be performed anytime, anywhere. It can reduce patients’ stress levels and negative emotions, improve their physiological and biochemical indicators, alleviate symptoms, help them better adapt to treatment, and improve their quality of life. The combination of progressive muscle relaxation and other intervention methods is more effective than using progressive muscle relaxation alone. Conclusion: The efficacy of progressive muscle relaxation is increasingly recognized, but its operating procedures need to be optimized and its combination with other therapies needs to be strengthened.